Problems 1, 2, and 3: I'm not sure I can rewrite these correctly, so I'll answer generally. It looks like each of these involve the order of operations, which is:

Parentheses, Exponents, Multiplication/Division (from left to right), Addition/Subtraction (from left to right).

So if problem 1 is **8 divided by 2 times 2 minus 3 to the 2nd power**,

this would look like 8 ÷ 2 * 2 - 3^{2}

By order of operations, we do the exponents (3^{2}) first, and we get

8 ÷ 2 * 2 - 9

Now we do multiplication and division as we encounter them from left to right. So first we tackle 8 ÷ 2 and rewrite our expression with the result

4 * 2 - 9

Now we have 4 * 2 (which equals 8), and we rewrite our expression again:

8 - 9

Now, there is nothing left but subtraction, and 8-9 = -1.

Given that explanation, see if you can apply this process to problems 2 and 3

You can remember the order of operations with the saying "Please Excuse My Dear Aunt Sally":

Please = Parentheses

Excuse = Exponents

My = Multiplication

Dear = Division

Aunt = Addition

Sally = Subtraction

Problem 4: If x = -3, then 4x^{2} - 3x - 10 = ?

Replace x in the expression with (-3), to get

4(-3)^{2} - 3(-3) - 10 = 4(9) + 9 - 10 = (I'll leave the final answer for you)

Problem 5: Since the board is cut into two pieces, let's let x = length of first piece and y = length of second piece. We then know that x + y = 8 feet

Since one piece is 2 feet longer than the other, let's assume that the first piece is longer than the second, so we now have a second equation, x = y + 2

Replace x in the first equation with y+2 (from the second equation), and we now have

(y+2) + y = 8

2y + 2 = 8

2y = 6

y = 3 . Since we assumed that y was the shorter board, this is our answer.

Problem 6: I'm reading this as (3x^{2}y)(2x^{3}y).

If so, we multiply common factors together:

(3*2)(x^{2}x^{3})(yy) = 6 x^{2+3}y^{1+1} = **
6x**^{5}y^{2}

Problem 7: If looks like the problem is 5a^{3} - 2a^{2} - (4a^{2} - 3). If so, then your answer is close, with one change:

The negative in front of (4a^{2} - 3) gets distributed across both terms within the parentheses. So if we cleared the parens, our expression would look like

5a^{3} - 2a^{2} + (-1)( 4a^{2)} + (-1)(- 3) = 5a^{3} - 6a^{2}
**+ 3**

## Comments

can you help me